At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find and simplify [tex]\((f + g)(2)\)[/tex], we start by evaluating each function at [tex]\(x = 2\)[/tex].
First, we'll evaluate [tex]\(f(2)\)[/tex]:
[tex]\[ f(x) = -3x^2 + 3x + 3 \][/tex]
Substitute [tex]\(x = 2\)[/tex]:
[tex]\[ f(2) = -3(2)^2 + 3(2) + 3 \][/tex]
Calculate the squares and the products:
[tex]\[ f(2) = -3(4) + 6 + 3 \][/tex]
[tex]\[ f(2) = -12 + 6 + 3 \][/tex]
Combine the constants:
[tex]\[ f(2) = -12 + 9 = -3 \][/tex]
Next, we'll evaluate [tex]\(g(2)\)[/tex]:
[tex]\[ g(x) = 3x - 4 \][/tex]
Substitute [tex]\(x = 2\)[/tex]:
[tex]\[ g(2) = 3(2) - 4 \][/tex]
Calculate the product:
[tex]\[ g(2) = 6 - 4 \][/tex]
Combine the constants:
[tex]\[ g(2) = 2 \][/tex]
Now, to find [tex]\((f + g)(2)\)[/tex], we add the values of [tex]\(f(2)\)[/tex] and [tex]\(g(2)\)[/tex]:
[tex]\[ (f + g)(2) = f(2) + g(2) \][/tex]
Substitute the values we found:
[tex]\[ (f + g)(2) = -3 + 2 \][/tex]
Combine the constants:
[tex]\[ (f + g)(2) = -1 \][/tex]
Thus, the simplified value of [tex]\((f + g)(2)\)[/tex] is [tex]\(-1\)[/tex].
First, we'll evaluate [tex]\(f(2)\)[/tex]:
[tex]\[ f(x) = -3x^2 + 3x + 3 \][/tex]
Substitute [tex]\(x = 2\)[/tex]:
[tex]\[ f(2) = -3(2)^2 + 3(2) + 3 \][/tex]
Calculate the squares and the products:
[tex]\[ f(2) = -3(4) + 6 + 3 \][/tex]
[tex]\[ f(2) = -12 + 6 + 3 \][/tex]
Combine the constants:
[tex]\[ f(2) = -12 + 9 = -3 \][/tex]
Next, we'll evaluate [tex]\(g(2)\)[/tex]:
[tex]\[ g(x) = 3x - 4 \][/tex]
Substitute [tex]\(x = 2\)[/tex]:
[tex]\[ g(2) = 3(2) - 4 \][/tex]
Calculate the product:
[tex]\[ g(2) = 6 - 4 \][/tex]
Combine the constants:
[tex]\[ g(2) = 2 \][/tex]
Now, to find [tex]\((f + g)(2)\)[/tex], we add the values of [tex]\(f(2)\)[/tex] and [tex]\(g(2)\)[/tex]:
[tex]\[ (f + g)(2) = f(2) + g(2) \][/tex]
Substitute the values we found:
[tex]\[ (f + g)(2) = -3 + 2 \][/tex]
Combine the constants:
[tex]\[ (f + g)(2) = -1 \][/tex]
Thus, the simplified value of [tex]\((f + g)(2)\)[/tex] is [tex]\(-1\)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.